2007
DOI: 10.1093/europace/eum059
|View full text |Cite
|
Sign up to set email alerts
|

The Arg389Gly β1-adrenergic receptor gene polymorphism and susceptibility to faint during head-up tilt test

Abstract: An association of positive tilt table testing to a single nucleotide polymorphism with a Gly to Arg switch at position 389 of the beta(1)AR was found. This polymorphism may contribute to susceptibility to faint during orthostatic challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 21 publications
1
26
0
2
Order By: Relevance
“…The few papers concerning the genetic predisposition to vasovagal syncope that have so far been published [17,18,22,24] have described associations between single nucleotide polymorphisms of genes influencing the adrenergic [17,18,22] and angiotensin pathways [24], but there are no studies exploring the genetic factors related to the endothelin system in patients with a history of unexplained syncope.…”
Section: Discussionmentioning
confidence: 99%
“…The few papers concerning the genetic predisposition to vasovagal syncope that have so far been published [17,18,22,24] have described associations between single nucleotide polymorphisms of genes influencing the adrenergic [17,18,22] and angiotensin pathways [24], but there are no studies exploring the genetic factors related to the endothelin system in patients with a history of unexplained syncope.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our data show that patients carrying the EDN1 4A allele are significantly more likely to develop vasodepressive syncope (type 3), thus suggesting that genetic altera- tions in the endothelin system may be associated with susceptibility to fainting during tilt testing by preferentially favoring depressor responses to orthostatic stress. The few papers concerning the genetic predisposition to vasovagal syncope that have so far been published [17,18,22,24] have described associations between single nucleotide polymorphisms of genes influencing the adrenergic [17,18,22] and angiotensin pathways [24], but there are no studies exploring the genetic factors related to the endothelin system in patients with a history of unexplained syncope.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, genetic studies showed association between certain single nucleotide polymorphisms and vasovagal syncope [11,12,14]. Both observations suggest a genetic basis for the condition.…”
Section: Introductionmentioning
confidence: 92%